Competency-Based Teaching in French as a Foreign Language Classrooms. A Case Study in Algerian Third-Year Secondary Education - Leila BOUCHEBCHEB (Eon)
This study examines the teaching and learning of competencies in third-year secondary education. We focus on the experiences of our pre-service teachers during their fieldwork to assess the role of the Competency-Based Approach (CBA) in official documents and student textbooks, to identify instructional strategies employed for its implementation, and to determine whether students effectively develop the competencies outlined in ministerial guidelines. To achieve this, we worked closely with our pre-service teachers and analyzed the various methods adopted by educators within the CBA framework. We developed three evaluation grids to compare the competencies featured in the official curriculum with those actually taught in FLE classrooms. This methodology allowed us to observe how teachers adapt their instructional practices to reconcile program requirements with real-world classroom constraints.